Kontribusi Perpustakaan Islam terhadap Era Renaisans di Eropa: Perspektif Historis - Sholihah, Husna Amalina; Sari, Khairunnisa Etika (Warisan: Journal of History and Cultural Heritage, 2023)
This article explores the vital role of Islamic libraries in transmitting scientific knowledge during the European Renaissance, contributing to Europe's modern-era advancement. Utilizing a qualitative approach with a historical literature review, the study analyzes data from various historical documents through heuristics, criticism, verification, interpretation, and historiography. It identifies three main channels for knowledge transfer from the East to the West: Andalusia, Sicily, and the Crusades. Andalusia, in particular, became a hub of scholarship and civilization, resulting in the translation and dissemination of diverse books, ultimately leading to the establishment of European universities. A parallel transformation occurred in Sicily, where an Islamic system persisted under Christian rule. The introduction of paper and the printing press facilitated the widespread dissemination of knowledge. Averroism, influenced by these developments, played a pivotal role in catalyzing the Renaissance, shaping Europe's trajectory towards exploration and global leadership in modern civilization. Islamic libraries' contributions in transmitting scientific knowledge significantly influenced the Renaissance, laying the foundation for Europe's subsequent achievements and leadership in the modern world.